1999
DOI: 10.1165/ajrcmb.20.1.3449
|View full text |Cite
|
Sign up to set email alerts
|

CD34+/Interleukin-5R α Messenger RNA+Cells in the Bronchial Mucosa in Asthma: Potential Airway Eosinophil Progenitors

Abstract: Eosinophil differentiation is thought to occur by the action of interleukin (IL)-5 on CD34(+) progenitor cells. The allergen-induced increase in eosinophil numbers in isolated airway preparations in vitro, and detection of increased numbers of circulating CD34(+) cells in atopic subjects, led us to the hypothesis that the eosinophil infiltration of the airway in asthma may result from local mucosal differentiation, in addition to recruitment from the bone marrow. We examined CD34(+) cell numbers by immunohisto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
116
0

Year Published

2000
2000
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 143 publications
(124 citation statements)
references
References 26 publications
6
116
0
Order By: Relevance
“…Presence of this additional eosinophil-differentiation pathway is supported by reports showing that allergic subjects have increased numbers of the eosinophil-lineage-committed CD34 ϩ cells in BM 12 and AW 13 and that AW CD34 ϩ cells can complete their differentiation following ex vivo stimulation with interleukin 5 (IL-5) or allergen. 14 However, whether these cells retain their ability to multiply within AW and subsequently maturate into eosinophils in vivo is not known.…”
Section: Introductionmentioning
confidence: 84%
See 1 more Smart Citation
“…Presence of this additional eosinophil-differentiation pathway is supported by reports showing that allergic subjects have increased numbers of the eosinophil-lineage-committed CD34 ϩ cells in BM 12 and AW 13 and that AW CD34 ϩ cells can complete their differentiation following ex vivo stimulation with interleukin 5 (IL-5) or allergen. 14 However, whether these cells retain their ability to multiply within AW and subsequently maturate into eosinophils in vivo is not known.…”
Section: Introductionmentioning
confidence: 84%
“…12 Subjects with asthma have increased numbers of these double-positive cells in the bronchial mucosa, 13 which argues that eosinophils could differentiate from CD34 ϩ cells locally within the AW. Supporting this hypothesis, however, there is only indirect evidence, such as increased expression of IL-5R␣ mRNA on CD34 ϩ cells within asthmatic bronchial mucosa 13 or simultaneous decrease in the number of CD34 ϩ /IL-5R␣ ϩ cells and increase in the number of major basic protein positive (MBP ϩ ) cells in allergic nasal tissue explants in response to rIL-5 or allergen. 14 In our study, we used 2 different methods to assess commitment of CD34 ϩ progenitor cells into eosinophil lineage, namely, coexpression of CD34 antigen and IL-5R␣ and, second, appearance of eosinophilic granulation on CD34 ϩ cells.…”
Section: Discussionmentioning
confidence: 99%
“…This prominently contributes to local eosinophilia, possibly via a feedback mechanism existing between the local tissue and BM, which triggers allergic inflammatory reaction [32][33][34]. Recent studies have shown that eosinophil precursors in BM are identifiable as CD34 + /IL-5R § + cells [35]. CD34 is an O-sialylated glycoprotein, whose expression within the hemopoietic system is restricted to primitive progenitor cells of all lineages [36], while IL-5R expression is essentially limited to eosinophil and basophil lineages [37,38].…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have shown that eosinophil colony-forming activity is increased in the peripheral blood of atopic asthmatic patients during the exacerbation of asthma (22). Furthermore, the number of circulating CD34 ϩ cells are increased in atopic subjects (14), and CD34 ϩ cells can also be detected in the bronchial mucosa in asthmatic subjects (40). Recently, a study has suggested that a subset of eosinophils in fact may differentiate in peripheral tissue such as the nasal mucosa (41) in a process that is highly IL-5 dependent.…”
Section: Discussionmentioning
confidence: 99%
“…The high expression of IL-5R ␣-chain in the bone marrow supports the concept that IL-5 is intricately involved in eosinophilopoiesis, and also one important effect of this cytokine is localized to immature eosinophils bearing IL-5Rs. In humans, it has been shown that mRNA specific for the ␣-chain of IL-5R can be found also in airway tissue (40,51), and it is possible that this mRNA expression leads to IL-5R expression on the cell surface. Certainly, it is likely that airway eosinophils do express small numbers of functionally active IL-5Rs, which, however, are impossible to stain by immunocytochemical techniques.…”
Section: Discussionmentioning
confidence: 99%